SATISFACTION WITH PERFORMANCE EVALUATION SYSTEMS APPLIED TO HEALTH PERSONNEL WORKING IN PRİVATE HOSPITALS AND AN EXAMPLE APPLICATION (Third Sector Social Economic Review, 2017)
Performance evaluation is the most important element of human resources functions. Because performance evalution it unites the individual and the organization in the direction of common goals and objectives. For this reason, measuring effectiveness and efficiency is of great importance.With globalization Performance appraisal has become important and the field of performance appraisal has begun to increase in the private sectorhe performance evaluation systems applied in the health sector show differences according to the institutions. In the private sector are being implemented a performance evaluation system that conforms with today's human resources practices .The health staff are the ones most affected by the performance evaluation results in the health sector.The aim of this study is to show the health staff satisfaction levels.In the research part of this study; by Çakmak and Biçer (2006) a literature review of performance appraisal by a review of studies performed previously in the field with a questionnaire that was used was created by. The survey probability sampling method in SPSS to healthcare personnel who work in the private sector by applying the results have been interpreted.
Keywords: Performance Evaluation; Health Sector; Health Personnel; Satisfaction; Human Resources Management.